Laser Distance-Based Digital Weight and Height Measurement System with Thermal Printer Output - Abidin, Muhammad Sainal; Adami , Aryani; Sutiari, Desak Ketut; Kasih, Ridia Utami (Sebatik, 2024)
The growth and development of a person's body can be influenced by various factors, including hereditary traits, environmental conditions, and dietary habits. One method to assess a person's physical growth and development is by comparing weight and height, commonly analyzed through the Body Mass Index (BMI). To perform this analysis, accurate measurements of weight and height are required. The tool developed in this study simplifies this process by enabling simultaneous measurement of weight and height. Weight measurement is conducted using a weight sensor (Load Cell) positioned under the user's footing, similar to a typical tire scale. Height measurement, on the other hand, utilizes a laser-based distance sensor (VL53L1X) placed above the patient's head. This approach differs from traditional height measurement methods that rely on sound-based distance sensors, which often yield less accurate results due to factors such as uneven head surfaces, varying hair textures, and diffused sound waves. To address these limitations, the developed system incorporates a Scale Bar or plate that moves up and down automatically, providing a flat, stable measurement plane. This ensures more precise height measurements by focusing the laser sensor's reflection on a uniform surface. From the results of measurements on several patients, the developed tool demonstrated an average difference of only 0.3 cm for height and 0.09 kg for weight, indicating high accuracy and reliability in body measurement.